Meningkatkan Hasil Belajar Passing Bolabasket Melalui Penerapan Pembelajaran Teams Game Tournement (TGT) Pada Siswa Smp Negeri 3 Ambon - Kubangun, Puspisa Sari Dewi; Unmehopa, Wilhelmina; Latar, Idris Moh (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2021)
This study aims to improve activities and learning outcomes of basketball passing techniques through the application of learning teams games tournament to class VIII students of SMP Negeri 3 Ambon. This research is classroom action research carried out in two cycles consisting of stages of planning, implementing action, observing and reflecting. The subjects of this study were 23 people. data were analyzed using descriptive statistics. Based on the results of data analysis in the first cycle, 6 students were active and in the second cycle, 23 were active. Classical learning completeness in the first cycle only 26% met the KKM standards and in the second cycle the attitude, knowledge and skill aspects were 100% in the very good category. Based on the results of data analysis and discussion it was concluded that the activity and learning outcomes of basketball passing techniques increased through the application of times game tournament (TGT) type of learning to class VIII students of SMP Negeri 3 Ambon.